China's environmental and climate change policies: China as an energy, environment and cultural superpower - Senz, Anja-Désirée (Idees, 2021)
Melanin in milk powder, cadmium in rice, malachite in seafood, lead in tea, carbamate in ginger, antibiotics in chicken meat, exploding water melons and cooking oil “recycled” from sewage - those are just some of numerous food scandals leaked out in recent years in China. They highlight various contaminations of water, air and soil equally as the weak points of political regulation. For many years, China has become a permanent feature on international debates on environmental and climate protection. The rapid economic development caused massive deterioration of the environmental conditions and because of high emissions China is considered to be…